Life satisfaction and job and personal resources among public workers with non-standard work schedules - Jennifer M. Cavallari; Sierra M. Trudel; Megan N. Miskovsky; Rick A. Laguerre; Alicia G. Dugan (BMC, 2024)
Abstract Background While the link between non-standard work schedules and poor health outcomes is established, few studies have examined how resources both in and outside of work can support the well-being of workers with non-standard work schedules. Methods Using a cross-sectional survey, we assessed the association between one facet of well-being, life satisfaction, and job and personal resources. In 2019, an electronic survey was administered to two unionized, public service populations who work non-standard work schedules: transportation maintainers and correctional supervisors. We assessed life satisfaction with a 10-item scale; a broad set of job resources (reward satisfaction, supervisor support, co-worker support, schedule satisfaction, and working hours fit); and a broad set of personal resources (health status, sleep, physical activity, and finances). We used log-binomial regression models to estimate prevalence ratios and 95% confidence intervals among statistically significant univariate predictors. Results Of the 316 workers surveyed, the majority were male (86%), White (68%), and reported positive life satisfaction (56%). In multivariate models, the prevalence of positive life satisfaction was higher in workers reporting reward satisfaction (PR:1.35, 95% CI: 1.11, 1.65; p = 0.003), good work schedule fit (PR:1.43, 95% CI: 1.12, 1.83; p = 0.004), good health (PR:2.92, 95% CI: 1.70, 4.99; p < 0.0001), and good finances (PR:1.32, 95% CI: 1.01, 1.72; p = 0.04). Conclusion Employers should consider increasing work recognition, as well as improving schedule fit, financial well-being, and overall good health in support of worker life satisfaction and ultimately well-being.